Gene delivery potential of bio functional carbonate apatite nanoparticles for lung cells - Alhaji, Suleiman Yusuf (2013)
Gene therapy has propelled innovations in therapeutic intervention of pulmonary related genetic diseases and cancer. However, lack of effective gene carrier system remains a major challenge in its clinical application. Carbonate apatite (CO3Ap) nanoparticles have been assessed in various gene delivery trials in mammalian cells with promising results. However, no study has been performed on the gene delivery potential of CO3Ap to lungs to date. Hence, this study aimed (1) to assess the gene delivery efficiency of CO3Ap in vitro and in mouse lungs via intranasal delivery, (2) to evaluate the cytotoxicity effect of CO3Ap/pDNA on the transfected lung cells and (3) to characterise the CO3Ap/pDNA complex formulations. Significantly high level of reporter gene expression was detected from lung cell line transfected with CO3Ap/pDNA complex prepared in medium with and without serum. Further transfection study using CO3Ap/pDNA complex formulation in 100 l serum free medium was investigated. This pre-dosing study aimed to mimic the amount of the complex formulation a mouse lung can accommodate. The reporter gene expression was found to be significantly higher than all the control groups when 8 µl of CaCl2 was used to prepare the CO3Ap [CO3Ap(8l)/pDNA]. Cytotoxicity analysis revealed that CO3Ap/pDNA was not toxic to the cells. The percentage of the viable cells was found to be almost similar to the untreated cells. As for the characterization analyses, it was found that (1) the CO3Ap/pDNA complex possesses aggregated spherical structure, particularly at higher concentration of CaCl2 in the CO3Ap formulations, (2) the CO3Ap/pDNA complex was within nanometer range, (3) the sizes of the CO3Ap particles were found to be proportional to the amount of CaCl2 in the CO3Ap formulations, (4) the CO3Ap/pDNA possesses negative surface charge and the charge densities tended to be more negative when high amount of CaCl2 in the CO3Ap was used in the formulations, and (5) the CO3Ap generated with 8 µl of 1M CaCl2 [CO3Ap(8l)] offered considerable protection of pDNA against degradation by a nuclease. In the lung of BALB/c mice, highest level of transgene expression was observed when CO3Ap(8l) was complexed with 40 µg of pDNA at day 1 post administration. Although massive reduction of gene expression was seen after day 1 post-administration, the levels remain significant through out the study time points. This indicates a prolonged gene expression property of the CO3Ap/pDNA in the mouse airways.